Agility in Young Athletes: Is It a Different Ability From Speed and Power?. Issue 3 (March 2017) - Negra, Yassine; Chaabene, Helmi; Hammami, Mehréz; Amara, Samiha; Sammoud, Senda; Mkaouer, Bessem; Hachana, Younés
Abstract: Negra, Y, Chaabene, H, Hammami, M, Amara, S, Sammoud, S, Mkaouer, B, and Hachana, Y. Agility in young athletes: is it a different ability from speed and power? J Strength Cond Res 31(3): 727–735, 2017—Agility is an important physical attribute for successful participation in team sports events. Illinois agility test (IAT) and T-test have been widely used within adult team sports players to assess agility performance. The purposes of this investigation are (a) to study the reliability and the sensitivity of both IAT and T-test scores and (b) to explore to what extend the agility is an independent physical ability from speed time and jumping ability. Competitive-level young soccer ( n = 95) and handball players ( n = 92) participated in this study (i.e., approximately 12 years old). Reliability analyses were established by determining intraclass correlation coefficient (ICC(3, 1) ) and typical error of measurement (TEM). The sensitivity of agility tests was revealed by comparing TEM to the value of the smallest worthwhile change (SWC). The second aim was examined by means of the principal component analysis. Results revealed that the scores of both IAT and T-test showed a high reliability (all ICC(3, 1) > 0.90 and TEM < 5%) and sensitivity (all TEM < SWC). Principal component analysis resulted in one significant component for the soccer and handball group each that explained 72.18 and 80.16% of the total variance, respectively. Significant relationships were recorded between all the selected tests ( r = −0.72 to 0.85, p < 0.001). Based on the results of this study, it was concluded that both IAT and T-test provided reliable and sensitive scores. Therefore, these tests could be strongly recommended to evaluate agility within young male competitive-level team sports athletes. In addition, it seems that agility, speed time, and jumping ability assess the same physical attribute in young competitive-level team sports players.